Natural Drug-Loaded Bimetal-Substituted Hydroxyapatite-Polymeric Composite for Osteosarcoma-Affected Bone Repair - Wang, Yanjun; Yao, Yongfeng; Thirumurugan, Muthupandi; Prabakaran, Selvakani; Rajan, Mariappan; Wang, Kai (Frontiers in Cell and Developmental Biology, 2021)
Repairing segmental bone deformities after resection of dangerous bone tumors is a long-standing clinical issue. The study’s main objective is to synthesize a natural bioactive compound-loaded bimetal-substituted hydroxyapatite (BM-HA)-based composite for bone regeneration. The bimetal (copper and cadmium)-substituted HAs were prepared by the sol-gel method and reinforced with biocompatible polyacrylamide (BM-HA/PAA). Umbelliferone (UMB) drug was added to the BM-HA/PAA composite to enhance anticancer activity further. The composite’s formation was confirmed by various physicochemical investigations, such as FT-IR, XRD, SEM, EDAX, and HR-TEM techniques. The bioactivity was assessed by immersing the sample in simulated body fluid for 1, 3, and 7 days. The zeta potential values of BM-HA/PAA and BM-HA/PAA/UMB are −36.4 mV and −49.4 mV, respectively. The in vitro viability of the prepared composites was examined in mesenchymal stem cells (MSCs). It shows the ability of the composite to produce osteogenic bone regeneration without any adverse effects. From the gene expression and PCR results, the final UMB-loaded composite induced osteogenic markers, such as Runx, OCN, and VEFG. The prepared bimetal substituted polyacrylamide reinforced HA composite loaded with UMB drug has the ability for bone repair/regenerations.